PENGEMBANGAN PERANGKAT LUNAK APLIKASI ANALYTIC HIERARCHY PROCESS (AHP) PADA MANAJEMEN PERAWATAN UNTUK MENENTUKAN STRATEGI PERAWATAN YANG TEPAT PADA MESIN-MESIN PRODUKSI (Studi Kasus PT. Coca-Cola Amatil Semarang) - , Putu Fransisca P, Hari Agung Yuniarto, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Maintenance and risk are important in managing production assets. The appropriate maintenance system is nessasary applied to increase productivity in production process. Maintenance strategy needs to be considered carefully in line with factors that affect the condition of the equipment. Unfortunately, there are many industries still make mistakes in determining the maintenance strategy. This is presumably because the people who work in maintenance has not been applied the optimal maintenance strategy because they think it is complex to be studied and applied in each machines as well as the unavailability a tool for simplifying the maintenance strategy. In this study, researchers want to facilitate the user in decision making of maintenance strategy. Researchers create decision making tool using the Analytic Hierarchy Process (AHP). By organizing and assessing alternatives to the multifaceted hierarchy, AHP provides an effective verification to handle decision complexity. The software is designed to accommodate the user needs in making for maintenance strategy on critical and non critical machine. The information will be used by user to optimalize the maintenance actions. The research was carried out with a case study in PT. Coca-Cola Amatil Semarang. Software making is done in Department of Mechanical and Industrial Engineering, Faculty of Engineering, Gadjah Mada University and PT. Coca-Cola Amatil Semarang. Data retrieval and process of software testing is done in PT. Coca-Cola Amatil Semarang. The results is software named DEFORMEST (Decision for Maintenance Expert Software). Preliminary testing results indicate that the selected maintenance strategy to address the critical machine is preventive maintenance based on global weight 0.5596. Maintenance strategy to address the non critical machine is preventive maintenance based on global weight 0.3303. Proven software can be applied well in PT. Coca-Cola Amatil Semarang. This can be informed by increasing the efficiency of machines in Line 5. Net Line Efficiency increased by 3.65 % and Gross Line Efficiency increased by 3.13 %. In addition, the Operation Performance Loss decreased by 4.56.